Description of Sergentomyia (Parrotomyia) rectangulata sp. nov. (Diptera: Psychodidae: Phlebotominae) from southern India - Srinivasan Renganathan; Jambulingam Purushothaman (Memorias do Instituto Oswaldo Cruz, 2010)
Both sexes of Sergentomyia (Parrotomyia) rectangulata sp. nov. from southern India are described with illustrations. The specimens were collected in tree holes, termite mounds, cattle sheds and mud-walled, thatched roof human dwellings in rural areas. Our findings reveal similarity with Sergentomyia (Parrotomyia) modii Lewis.